Biodiversity of Medicinal Plants at Sambas Botanical Garden, West Kalimantan, Indonesia - Sudarmono, Sudarmono (Journal of Tropical Life Science, 2018)
Botanical garden is one of ex-situ conservation which has function as germ plasm conservation, education/research, and recreation. To conserve plants biodiversity, many local governments in Indonesia propose to cooperate with LIPI to build botanical gardens. Sambas botanical garden with an area Â± 300 ha in West Kalimantan is one of a botanical garden which is under construction. As new exploration site, many biodiversity in this area has not been entirely explored yet including its medicinal plants. Methods used in this study including field survey and interview techniques. The objective of this study is to explore a biodiversity of medicinal plants in that area. This study identified 30 medicinal plants, representing 20 families and 25 genera. It indicated that Sambas botanical garden has many highly potential values of medicinal plants. Therefore, a proper management including medicinal plant for this area is strongly required.Â